2021
DOI: 10.1051/e3sconf/202123101004
|View full text |Cite
|
Sign up to set email alerts
|

Why should the automated guided vehicles’ batteries be used in the manufacturing plants as an energy storage?

Abstract: This paper examines to what extent automated guided vehicles’ (AGV) batteries can be used as a mobile electrical energy storage to increase energy flexibility and reduce peak loads in manufacturing plants. First, it is indicated, what demand response and peak shaving in manufacturing mean. Then, existing battery applications for peak shaving are presented. Finally, the benefits and potential of using AGVs as energy storage to reduce peak loads in the company are illustrated, after an approximate cost calculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Current research [44][45][46][47][48][49][50] analyzes the charging voltage curves to study the battery characteristics. The DC charging voltage curve can be used to analyze the mechanisms of battery aging and degradation, as well as to assess the condition of a battery.…”
Section: State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research [44][45][46][47][48][49][50] analyzes the charging voltage curves to study the battery characteristics. The DC charging voltage curve can be used to analyze the mechanisms of battery aging and degradation, as well as to assess the condition of a battery.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Publication [50] explores the use of AGV batteries as portable energy storage devices to reduce peak loads at manufacturing enterprises. For this purpose, scenarios were created to determine the electricity costs of small and medium-sized enterprises.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Notable studies include Vitalii et al (2021), which found that replacing human-controlled vehicles with autonomous mobile robots could significantly reduce energy consumption, even without modifying the control system. Ozan et al (2021) explored reducing peak loads and lowering energy costs for companies implementing AGVs in their production processes. Additionally, several other relevant studies on the subject include Guilherme et al (2019), which focused on the sustainable implementation of AGVs in the Brazilian industry; Puneeth et al (2018), which examined the size of AGV fleets and their impact on operations; and Hee-Woon and Hwally (2018), which looked at the efficiency of AGVs for small businesses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Peak shaving can be a lucrative way to save on electricity costs [7]. Using forecasts, peak shaving aims to reduce current load peaks and thus reduce grid charges.…”
Section: Introduction 1motivation and Problem Formulationmentioning
confidence: 99%